2010
DOI: 10.1051/limn/2010006
|View full text |Cite
|
Sign up to set email alerts
|

Variation in the growth ofMicrocystis aeruginosadepending on colony size and position in colonies

Abstract: -Growth of colonial Microcystis aeruginosa was investigated by performing an incubation experiment. Colonies of M. aeruginosa were separated based on size (colony diameter <100 mm, 100-200 mm and > 200 mm) by filtration. Additionally, the cells around the surface of the colonies were separated from those inside the colonies by short-term ultrasonic treatment followed by filtration. Experimental results indicate that M. aeruginosa grew continuously throughout a 35-day incubation period in a nutrient-rich medium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 18 publications
0
16
1
Order By: Relevance
“…As also observed in this study, the relative abundances of cyanobacteria in waters with very high nutrient concentrations were generally small; in such cases, diatoms and/or green algae commonly dominated. Yamamoto and Shiah (2010) suggested that the active growth of M. aeruginosa occurs mainly inside colonies, and when the growth of these cells begins to be suppressed as a result of self-shading, peripheral cells separate as smaller colonies. Since the growth rate of small colonies exceeds that of peripheral cells, this growth mechanism enables a population of M. aeruginosa to maintain high growth activity (Yamamoto and Shiah, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As also observed in this study, the relative abundances of cyanobacteria in waters with very high nutrient concentrations were generally small; in such cases, diatoms and/or green algae commonly dominated. Yamamoto and Shiah (2010) suggested that the active growth of M. aeruginosa occurs mainly inside colonies, and when the growth of these cells begins to be suppressed as a result of self-shading, peripheral cells separate as smaller colonies. Since the growth rate of small colonies exceeds that of peripheral cells, this growth mechanism enables a population of M. aeruginosa to maintain high growth activity (Yamamoto and Shiah, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Yamamoto and Shiah (2010) suggested that the active growth of M. aeruginosa occurs mainly inside colonies, and when the growth of these cells begins to be suppressed as a result of self-shading, peripheral cells separate as smaller colonies. Since the growth rate of small colonies exceeds that of peripheral cells, this growth mechanism enables a population of M. aeruginosa to maintain high growth activity (Yamamoto and Shiah, 2010). The present study revealed that large colonies of M. aeruginosa formed only when this species exclusively dominated the community of photosynthetic plankters; the colonies were not significantly large even when the cyanobacterium accounted for 54.1 or 85.2% of the total biovolume of the photosynthetic plankters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these factors, the uptake and utilization of dissolved inorganic carbon (DIC) are thought to be critical factors (Yamamoto & Shiah, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The remarkable effects of physical disturbance on Microcystis and Oscillatoria in this work explained the better recruitment of cyanobacteria under disturbance, fitting well with physiological research on Microcystis recruitment. [47,48] The aerobic environment created by physical disturbance benefited their resuscitation from the sediment into water body. [49] It was reported that the single vertical convection type of water temperature in Shanzi reservoir could form a stable thermal stratification from March to November.…”
Section: Cyanobacterial Community Structure At Water-sediment Interfacementioning
confidence: 99%